The taxonomic position of Carabus (Morphocarabus) kozhantschikovi Lutshnik, 1924 and Carabus (Morphocarabus) odoratus Motchulsky, 1844 (Coleoptera: Carabidae) - Obydov, Dmitry (Acta entomologica slovenica (Ljubljana), 1999)
Two Siberian species, C. kozhantschikovi Lutshnik, 1924 and C. odoratus Motschulsky, 1844, are examined. C. odoratus martjanovianus ssp. n. from western Sayans is described. Diagnostic data are given. The endophallus of C. kozhantschikovi, not previously figured, is illustrated.
Keywords: entomologija; hrošči; zoologija; zoology